(untitled) (Universal International Scientific Journal, 2026)
This article discusses the understanding of the concept of social norms in society during the Information Age, behavioral disorders in adolescents. It discusses quadrobics and therianthropy, which are considered one of the negative aspects of the globalization process, and measures to prevent them.